2013
DOI: 10.4161/cc.23406
|View full text |Cite
|
Sign up to set email alerts
|

TLR2 enhances ovarian cancer stem cell self-renewal and promotes tumor repair and recurrence

Abstract: Primary ovarian cancer is responsive to treatment, but chemoresistant recurrent disease ensues in majority of patients. Recent compelling evidence demonstrates that a specific population of cancer cells, the cancer stem cells, initiates and sustains tumors. It is therefore possible that this cell population is also responsible for recurrence. We have shown previously that CD44+/MyD88+ epithelial ovarian cancer stem cells (CD44+/MyD88+ EOC stem cells) are responsible for tumor initiation. In this study, we demo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
82
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 91 publications
(86 citation statements)
references
References 57 publications
4
82
0
Order By: Relevance
“…We previously showed that TLR2/MyD88 signaling in tumor cells promotes gastric tumorigenesis in gp130 F/F mice (19,28). Consistent with these findings, it has been shown that TLR2 signaling in cancer cells plays a tumor-promoting role through the enhancement of stemness (23,24). Moreover, the epithelial cell-specific deletion of Myd88 was observed to suppress intestinal tumorigenesis in Apc Min mice (16).…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…We previously showed that TLR2/MyD88 signaling in tumor cells promotes gastric tumorigenesis in gp130 F/F mice (19,28). Consistent with these findings, it has been shown that TLR2 signaling in cancer cells plays a tumor-promoting role through the enhancement of stemness (23,24). Moreover, the epithelial cell-specific deletion of Myd88 was observed to suppress intestinal tumorigenesis in Apc Min mice (16).…”
Section: Discussionsupporting
confidence: 59%
“…Importantly, we show that MyD88 signaling in BMDCs is required for the generation of the inflammatory microenvironment in tumors even though the COX-2/PGE 2 pathway is activated. Moreover, inflammatory responses induce the expression of TLR2 and CD14 in tumor epithelial cells, which have been shown to play tumor-promoting roles through enhancement of stem cell properties (16,23,24). These results indicate that both the MyD88 signaling and the COX-2/PGE 2 pathway are required for generation of the inflammatory microenvironment, which may promote tumorigenesis through the induction of TLR2/ CD14 signaling in tumor cells.…”
Section: Introductionmentioning
confidence: 68%
“…Current studies suggest that recurrence is caused by the regrowth of the surviving inherently chemoresistant cancer stem cells that persisted during chemotherapy. The expansion of this chemoresistant cancer cell population, coupled with prosurvival modifications induced by the pressure of treatment, is thought to be responsible for the development of chemoresistant recurrent disease (10). Heterogeneity of ovarian tumors is not only limited to the presence of different epithelial cell subtypes with differential stemness potential, but also in the presence of different cancer cells with varying stages of mesenchymal status and migratory/invasiveness potential (9,47).…”
Section: Discussionmentioning
confidence: 99%
“…These patient samples were obtained from patients at Yale New Haven Hospital (New Haven, CT) who were diagnosed with stage III/IV serous ovarian cancer and propagated as described previously (9,10,14,(28)(29)(30)(31)(32)(33) …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation